1992
DOI: 10.1007/bf00128769
|View full text |Cite
|
Sign up to set email alerts
|

Super-unstable mutations associated with P-M hybrid dysgenesis in Drosophila melanogaster

Abstract: Super-unstable mutations occasionally appear either in natural populations of Drosophila melanogaster or in P-M hybrid dysgenesis. We found that they may be reproducibly obtained with a high frequency from crosses between males from the pi 2 strain and females from the waG* strain or its derivatives. Super-unstable mutations in the ocelliless, singed, white, yellow and other loci have been obtained. Each super-unstable mutation gives rise to a large family of new super-unstable mutations with a wide range of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The null allele observed in a laboratory stock (JOHNSON et al 1966) may represent a spontaneous null mutation that would have very low probability to survive in nature. It may be likely that this spontaneous null mutation arose as a consequence of hybrid dysgenesis (Smn 1979;PRUD-HOMMEAU and PROUST 1990;GEORGIEV and YELAGIN 1992), which increases mutation rates in specific crosses that involve strains long cultured in the laboratory. In addition to the Est-6 null allele, JOHNSON et al (1966) found another null allele for a separate esterase locus, Est-C in the same D. melanogaster stock.…”
Section: Y D N P T D S O V O Q L L S N R ~---V H P G T V H G D D F F ...mentioning
confidence: 99%
“…The null allele observed in a laboratory stock (JOHNSON et al 1966) may represent a spontaneous null mutation that would have very low probability to survive in nature. It may be likely that this spontaneous null mutation arose as a consequence of hybrid dysgenesis (Smn 1979;PRUD-HOMMEAU and PROUST 1990;GEORGIEV and YELAGIN 1992), which increases mutation rates in specific crosses that involve strains long cultured in the laboratory. In addition to the Est-6 null allele, JOHNSON et al (1966) found another null allele for a separate esterase locus, Est-C in the same D. melanogaster stock.…”
Section: Y D N P T D S O V O Q L L S N R ~---V H P G T V H G D D F F ...mentioning
confidence: 99%